2021
DOI: 10.1073/pnas.2102434118
|View full text |Cite
|
Sign up to set email alerts
|

The macrophage odorant receptor Olfr78 mediates the lactate-induced M2 phenotype of tumor-associated macrophages

Abstract: Expression and function of odorant receptors (ORs), which account for more than 50% of G protein–coupled receptors, are being increasingly reported in nonolfactory sites. However, ORs that can be targeted by drugs to treat diseases remain poorly identified. Tumor-derived lactate plays a crucial role in multiple signaling pathways leading to generation of tumor-associated macrophages (TAMs). In this study, we hypothesized that the macrophage OR Olfr78 functions as a lactate sensor and shapes the macrophage–tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 51 publications
3
55
0
Order By: Relevance
“…Previous studies and our analysis show that high levels of OR51E2 expression were also associated with poor prognosis in breast cancer patients ( Fig. 2A ) ( 25 ).…”
Section: Or Expression In Various Types Of Cancersupporting
confidence: 69%
See 3 more Smart Citations
“…Previous studies and our analysis show that high levels of OR51E2 expression were also associated with poor prognosis in breast cancer patients ( Fig. 2A ) ( 25 ).…”
Section: Or Expression In Various Types Of Cancersupporting
confidence: 69%
“…Compared with xenografts of LLC murine Lewis lung carcinoma cell on wild-type mice, xenografts of these cells on mice with knockout of Olfr78, a mouse analog of OR51E2, showed reduced tumor growth and metastasis. In addition, TCGA analysis showed that lower OR51E2 expression correlated significantly with better survival ( 25 ). Solid-phase microextraction GC/MS identified a cancer-specific odorant, 2-ethyl-1-hexanol, in the SK-MES cancer cell line, and screening of human ORs found that OR4D11P was a sensitive and selective receptor of 2-ethyl-1-hexanol ( 49 ).…”
Section: Or Expression In Various Types Of Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Given that ORs may have potential oncogenic roles in solid tumors, and that ORs expressed in normal brain and during neurodegenerative disease have functions distinct from odor perception, we hypothesized that ectopic ORs would perform tumor-related functions in brain. As further evidence for the role of ectopic ORs in tumor-related functions in brain, we previously reported that Olfr78 (human homolog, OR51E2) induced M2 polarization, thereby promoting tumor progression and metastasis ( 49 ). M2-like tumor-associated macrophages are abundant in the glioma microenvironment, and mediate increased resistance to radiotherapy and immunotherapy ( 50 - 52 ).…”
Section: Main Textmentioning
confidence: 92%